The Role of The Production Cost Budget in Supporting The Effectiveness of Production Cost Control in CV. Cita Mandiri, Batu City - Patrisia Nimat Jematu; Elly Lestari; Anung Prasetyo Nugroho (International Journal of Management and Business, 2025)
The purpose of this study is to determine the role of the production cost budget in supporting the effectiveness of production cost control in CV. Cita Mandiri Batu City. This research uses a qualitative method. The data used was an interview with the leader and one of the employees in the production field at CV. Cita Mandiri Batu City. The data analysis method used is descriptive. The results of the description analysis prove that the process of preparing the production cost budget carried out by CV. Cita Mandiri Batu City is to determine production needs by detailing the cost of raw materials, detailing labor costs and operational costs. The details of the production cost budget are the cost of raw materials per production of Rp. 2,733,000, the cost of labor per production of Rp. 500,000 and the overhead cost of the factory (additional costs) per production of Rp. 151,500, meaning the total cost of production materials in one production on CV. Cita Mandiri Batu City as much as Rp.3.384,500. The results of the study prove that CV. Cita Mandiri Kota Batu is very effective in controlling production costs with a profit of 127,64% in one production, because the income is higher than the cost of production. Costs incurred by CV. Cita Mandiri Kota Batu in one production is IDR 3.384,500, the revenue obtained in one production is IDR 4.320.000 and the net profit obtained in one production is IDR 935.500. The importance of controlling production costs to increase income and improve CV progress. Cita Mandiri Batu City.